Product Market Reforms in Greece: Unblocking Investments and Exports - Kaspar Richter; Gabriele Giudice; Angelo Cozzi (Vierteljahrshefte zur Wirtschaftsforschung, 2015)
While Greece's poor record on investment and exports predates the crisis, the deep economic recession has made addressing long-standing weaknesses a priority. This paper takes a closer look at selected structural reforms that are critical for bolstering investments and exports in Greece. We investigate the areas of licensing, competition, professions, land use, and trade facilitation. In all areas significant progress has been made since 2010. However, many reforms are only partially implemented and with delays. Based on the challenges at, and progress since, the outset of the crisis, we chart the way forward in each of the five areas, discussing what needs to be done to improve the patchy reform record, thus unblocking investment and exports for Greece.
Keywords: J44; K23; O24; O52; R52; 330; Barriers to competition; business licensing; Greece; land use; structural reforms; trade facilitation